ANALISIS PEMILAHAN MODA TRANSPORTASI PENUMPANG ANTARA BUS DAN KERETA API RUTE MALANG-SURABAYA (STUDI KASUS BUS PATAS DAN KERETA API JAYABAYA) - -, M. Sadillah; Primasworo, Rifky Aldila; Egar, Flafianus (Universitas Islam Balitar Blitar, 2024)
Several modes transportation that developing at this time include the Patas Bus and Jayabaya Train which serve Malang-Surabaya route. In this study, authors conducted an analysis people's reasons for choosing the mode transportation between Patas Bus and Jayabaya Train malang - Surabaya. The this study was to determine the characteristics and modes transportation. Then we get the difference between Travel Expenses (∆X1) = UBUS-UKA = 20.509-0.196 , Difference in Travel Time (∆X2) = UBUS-UKA = 17.167-2.020, Difference in Travel Frequency (∆X3) = UBUS - UKA = 19.772 - 2.011 , Access Time Difference (∆X4) = UBUS – UKA = 33,662 – 1,136.